MRI Evaluation of Various Elbow, Forearm, and Wrist Neuropathies: A Pictorial Review - Husain, Rola; Reddy, Arthi; Dayan, Etan; Huang, Mingqian; Corcuera-Solano, Idoia (Seminars in Musculoskeletal Radiology, 2021)
Upper extremity entrapment neuropathies are common and can cause pain, sensory loss, and muscle weakness leading to functional disability. We conducted a retrospective review from January 2007 until March 2020 of the magnetic resonance imaging (MRI) features of intrinsic and extrinsic causes of wrist, forearm, and elbow neuropathies of 637 patients who received a diagnosis of neuropathy by means of clinical and electrodiagnostic testing. We discuss cases with varying intrinsic and extrinsic nerve pathologies, including postoperative examples, affecting the median, radial, and ulnar nerve.Our collection of cases demonstrates a diversity of intrinsic and extrinsic causative factors. Intrinsic pathologies include neuritis as well as tumors arising from the nerve. Extrinsic causes resulting in nerve entrapment include masses, acute and chronic posttraumatic cases, anatomical variants, inflammatory and crystal deposition, calcium pyrophosphate deposition disease, and dialysis-related amyloidosis. Finally, we review postsurgical cases, such as carpal tunnel release and ulnar nerve transposition.Although upper extremity neuropathies tend to have a typical clinical presentation, imaging, particularly MRI, plays a vital role in evaluating the etiology and severity of each neuropathy and ultimately helps guide clinical management.
Keywords: neuropathy; wrist; forearm; elbow; magnetic resonance imaging